How national culture and ethics matter in consumers' green consumption values. (20th August 2020) - Halder, Pradipta; Hansen, Eric N.; Kangas, Jyrki; Laukkanen, Tommi
Abstract: Going green in consumption is gaining momentum globally, but little is known how national cultural values and consumers' ethical ideologies explain green consumption. With a culturally rich sample of 1929 responses from consumers in Finland, Germany, Portugal, and the United Kingdom, the present study examines how cultural long-term orientation and collectivism predict consumers' green consumption values, and if these relationships are moderated by ethical ideologies. The study finds that cultural collectivism has a significant positive effect on green consumption values, as expected. However, the results show that the two long-term orientation constructs, namely planning and tradition, point in opposite directions when predicting green consumption. We demonstrate that while long-term planning has a significant positive effect on green consumption values, the effect of traditional values is negative. We further show that this negative effect varies across consumers' ethical ideologies so that the effect is the greatest for Exceptionists and Absolutists, that is, those who rely in their actions on universal moral principles rather than particular circumstances. Therefore, our research contributes to the literature by providing new evidence for the cultural and ethical aspects in green consumption values. Furthermore, the study suggests that managers pay special attention to the consumers who have high collectivistic and future-oriented values to promote environmentally friendly consumption. Highlights: Article examines the effects of national culture and moderating role of ethics on consumers' green consumption values. Cultural collectivism predicts consumers' green consumption values. Cultural long-term orientation shows mixed effects of planning and tradition. Planning and collectivism have greatest effects on green consumption values among exceptionists and subjectivists.